PROFILE OF PROSPECTIVE TEACHERS’ ERRORS IN CONTRUCTING MATHEMATICS PROOF USING COUNTEREXAMPLES - Rudi Santoso Yohanes (MATEMATIKA DAN PEMBELAJARAN, 2022)
Problems often encountered in mathematics are problems to prove and problems to find. Proving ability is very important, but it is still a weakness for most Mathematics Education students at Widya Mandala Catholic University Surabaya. This study describes the error profile of prospective teacher students in constructing mathematical proofs by using counterexamples and the factors suspected to be the cause of the error. This is exploratory-descriptive qualitative research, with six subjects of PSDKU Mathematics Education UKWMS who have taken Mathematical Logic and Set Theory. Data was collected using a test technique, the Mathematical Proof Ability Test, which was a subjective test consisting of 5 questions. The results of student work are then analyzed to describe the errors made by students in constructing mathematical proofs using counterexamples. The results showed that the errors made by students were: (1) errors in using the method of proof; (2) errors in using fundamental mathematical theorems; (3) errors in understanding the problem. The factors that are suspected to be the cause of student errors are: (1) students have a poor understanding of mathematical concepts; (2) students do not master the method of proof needed as a guide in carrying out mathematical proofs; (3) students do not have enough practice so they lack experience in constructing mathematical proofs by using counterexamples.